Lightweight Contextual Ranking of City Pictures: Urban Sociology to the Rescue - Zambaldi, Vinícius; Pesce, Joao; Quercia, Daniele; Almeida, Virgilio (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
To increase mobile user engagement, photo sharing sites are trying to identify interesting and memorable pictures. Past proposals for identifying such pictures have relied on either metadata (e.g., likes) or visual features. In practice, techniques based on those two inputs do not always work: metadata is sparse (only few pictures have considerable number of likes), and extracting visual features is computationally expensive. In mobile solutions, geo-referenced content becomes increasingly important. The premise behind this work is that pictures of a neighborhood is linked to the way the neighborhood is perceived by people: whether it is, for instance, distinctive and beautiful or not. Since 1970s, urban theories proposed by Lynch, Milgram and Peterson aimed at systematically capturing the way people perceive neighborhoods. Here we tested whether those theories could be put to use for automatically identifying appealing city pictures. We did so by gathering geo-referenced Flickr pictures in the city of London; selecting six urban qualities associated with those urban theories; computing proxies for those qualities from online social media data; and ranking Flickr pictures based on those proxies. We find that our proposal enjoys three main desirable properties: it is effective, scalable, and aware of contextual changes such as time of day and weather condition. All this suggests new promising research directions for multi-modal learning approaches that automatically identify appealing city pictures.